IMPACT OF AGRO-TOURISM ON LOCAL AGRICULTURAL OCCUPATION: A CASE STUDY OF CHANG KLANG DISTRICT, SOUTHERN THAILAND - SONGKHLA, TEPPAKORN NA (ASEAN Journal on Hospitality and Tourism, 2012)
Agro-tourism has been a priority as a means for improving the livelihood of agriculturist developing countries. Pragmatically, this promotion is associated with multiple functional agriculture in the context of local agricultural occupation. The purpose of this paper is to present the feature of agro-tourism activities and its impacts on local agricultural occupation. A case study of Chang Klang district, a well known community-based agro-tourism in Thailand shown that tourist farms operated agrotourism as the activities of demonstration, giving knowledge, selling local productions, and agri-business guidance. Over the past ten years of such promotions, within farms, local agricultural occupation relies on agricultural incomes from both agro-tourism activities and agricultural productions. During that time, agro-tourism significantly causes local agricultural occupation as agricultural service activities for a part of tourism. Now, according to instability of tourism market, local agricultural occupation within tourist farms is adjusted to serve profits to both agricultural productions and tourism business. These findings can be suggested that existing local agricultural occupations which is a part of processing is demonstrated for tourism, is a form of agrotourism activities towards sustainable local agricultural resources usages.